Peningkatan Pelayanan Publik Pemerintah Desa Berbasis Digital di Desa Parit Keladi - Aminah, Siti; Turiman, Turiman; Saliro, Sri Sudono (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service (PkM) aims to increase the capacity of the apparatus of Parit Keladi Village, Sungai Kakap District, Kubu Raya Regency, in utilizing digital technology to support public services. The analysis of the situation shows that the village website has not been optimally managed, and the village does not have an official social media account, so the distribution of information and public services has not been effective. The implementation method uses an educational-participatory approach through training, simulation, and direct mentoring. Materials include website management, creative content creation strategies for social media, digital communication techniques, and information security. The results of PkM activities show an increase in the ability of village officials to manage websites which now contain profiles, agendas, financial reports, and online administrative services. The village's Instagram account has been successfully activated with relevant and interesting content, as well as increasing community interaction through digital channels. It is recommended to establish a sustainable village digital channel management team, periodic digital literacy training, integration of websites with online administration services, collaboration with the community in content production, and periodic evaluation of the performance of digital channels to maintain the effectiveness of public services.